Respiratory Symptoms and Pattern of Lung Functions Among Commercial Motorcyclists in Sagamu, Nigeria - Adefuye BO; Adefuye PO; Odusan O (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2015)
Background: The relationship between occupational exposure to air pollutants and poor respiratory health is known. The motorcyclists commonly seek medical care for respiratory diseases in Nigeria. Objective: To determine the prevalence of respiratory symptoms and the pattern of lung functions among commercial motorcyclists compared to control subjects. Method: The controlled cross-sectional study was conducted in Sagamu, an urban town in south-western, Nigeria. The commercial motorcyclists and the controls with similar age, non-smokers and same male sex were included in the study. The riders and controls recruited were non-smokers. A structured questionnaire approved by the British Medical Research Council/ATS (American Thoracic Society) was used. The pulmonary function tests were performed according to ATS recommendation. Results: A total of 200 subjects were studied: 100 were commercial motorcyclists and 100 were non-motorcyclist controls. Compared with the controls, the prevalence of cough (71% vs 21%) and sputum (67% vs 20%) was higher among the commercial motorcyclists. Twenty-one percent of the commercial motorcyclists had an obstructive ventilatory pattern compared to 13% of the control group. Conclusion: This study provides further evidence that commercial motorcyclists are exposed to occupational hazards which predisposed them to increased frequency of respiratory symptoms and impaired lung functions. Health education strategy may assist this group of workers and reduce the burden of respiratory disorders among them.